Positive and Limiting Aspects in the Work of Health Professionals in Prison Units (Global Journal of Medical Research, 2020)
This study aims to analyze the positive and limiting aspects in the work of health professionals in federal prison units. This is a descriptive exploratory qualitative study. The information was collected through semi-structured interviews with professionals from federal prison units, between the months of June and October 2018. The positive aspects related to work found in the results were: salary recognition and job stability; good interpersonal relationships with colleagues in the workplace; low activity demand in prison units; flexible work hours; and provision of adequate physical and material resources. The limiting aspects are: lack of professional recognition and appreciation; divergence between work performed and professional activity; violence, fear and appearance of health problems at work.
Keywords: health professionals; prisons; worker#x2019; s health